KEBUTUHAN MENGENALKAN MATEMATIKA ANAK USIA DINI MELALUI KEARIFAN LOKAL - Sufa, Feri Faila; Setiawan, M. Hery Yuli (Jurnal AUDI: Jurnal Ilmiah Kajian Ilmu Anak dan Media Informasi PAUD, 2024)
Mathematics is a basic skill that is important in all aspects of life. The low ability of Indonesian students needs to be assessed by the factors that influence it. This article aims to explain several factors that can be both an obstacle and a support in providing an introduction to mathematics in early childhood by utilizing local wisdom. The results show that the teacher's ability factor in learning is very important to present a pleasant learning experience through local wisdom in accordance with the character and needs of the child. Learning innovation needs to be done so that teaching mathematics at an early age does not become polemic and becomes a conflict between educational needs and the stage of development. Â